Stakeholders' perception of fund sourcing and utilization in Nigerian public universities (2012)
Funding of public utilities or sector programmes in Nigeria has been acknowledged as an endemic problem almost defying any solution, more so, in the face of privatisation of public sector projects. This paper examined how stakeholders in the Nigerian university public system. Relevant questions were raised and answered. Two public universities in Oyo state: one federal and one state owned were used in the study. Fund Sourcing and Utilisation in Nigerian Public Universities Stakelholder' Instrument (FSUNSI) to collect the data and these were analyzed using both descriptive and inferential statistics. Results were that there were leakages in spending funds in public universities in spite of the fact that financial resources made available by the proprietors were obviously inadequate, due to the fact that the system was not as transparent as it should be . Management and other stakeholder have different perceptions to a large extent. It was also obvious that the federally owned university was better managed financially, compared to its state counterpart. Stakeholders thus proffered that the financial expenditure model which can be transparently monitored by all stakeholders both within and without the system.